2016
DOI: 10.5222/jaren.2016.059
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation of Fatigue of the Patients Undergoing Coronary Artery By-pass Graft Surgery

Abstract: Araştırma koroner arter bypass greft cerrahisi geçiren hastaların yorgunluk durumundaki değişimin incelenmesi amacıyla yapıldı. Yöntem: Tek gruplu ön test/ son test düzende tanımlayıcı olarak yürütülen araştırma, İstanbul Avrupa yakasında özel bir hastanenin kardiyovasküler cerrahi servisinde yapıldı. Örneklemi hastanede son 6 ay içinde koroner arter bypass grefti ameliyatı geçiren 32 hasta oluşturdu. Veriler yapılandırılmış bilgi formu ve Piper Yorgunluk Ölçeği ile toplandı. Preoperatif dönemde uygulanan anke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Kaya and Sentura 26 found that fatigue began before surgery and increased mostly immediately after surgery. Rubin et al 27 revealed that patients who underwent a major surgery (abdominal, gynecology, or cardiovascular surgery) had higher fatigue levels than those who underwent an orthopedic surgery.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Kaya and Sentura 26 found that fatigue began before surgery and increased mostly immediately after surgery. Rubin et al 27 revealed that patients who underwent a major surgery (abdominal, gynecology, or cardiovascular surgery) had higher fatigue levels than those who underwent an orthopedic surgery.…”
Section: Discussionmentioning
confidence: 98%
“…Fatigue adversely affects patients’ physical and mental well-being, prolongs their recovery and length of hospital stay, and increases their stress response to surgical trauma. 25 , 26 …”
Section: Discussionmentioning
confidence: 99%
“…C determines whether individuals have a clear idea of what to do to stay healthy and to improve their health. 17 The fact that the media constantly mentions the protective measures and how the pandemic affects older individuals more severely may have contributed to the positive behaviors of our participants in this age group in terms of maintaining their health. Beside affecting individuals biologically, socially and psychologically, the pandemic also leads to negative economic outcomes.…”
Section: Discussionmentioning
confidence: 96%
“…16 Evaluation of health perceptions and health behaviors includes not only the biological dimension of health, but also the perceived well-being in physical, mental, social and functional aspects. 17 Given the importance of human psychological and behavioral factors in managing pandemics, it is very important to evaluate psychological and behavioral responses to the situation. show the groups that are the sources of difference; pHS: perception of Health Scale; CC: Center of control; C: Certainty; IH: Importance of health; SA: Self-awareness; KW: Kruskal-Wallis…”
Section: Discussionmentioning
confidence: 99%
“…14 In the perception of health, which indicates a person's beliefs about and evaluations of their general health status, the more focus is on the physical and mental components. 15 For instance, in a qualitative study conducted on the perceptions of health and disease of Jordanian mothers, the mothers emphasized their children's general psychological and mental wellbeing as an indicator of the children's health. 16 Perception of health is thus a concept which involves individual beliefs about health and the perception of being healthy.…”
Section: Introductionmentioning
confidence: 99%